(untitled) (Journal of Comparative & International Higher Education, 2024)
Chinese international students on U.S. college campuses often experience acculturative stress, a phenomenon concerned with adapting to a new culture. However, there is a paucity of research about how these students use culturally relevant strategies to cope with this stress and enhance their well-being. Based on Heppner et al.’s (2014) cultural and contextual model of coping, this study explores a three-way interaction between Chinese international students’ acculturative stress, proactive coping, and future time perspective in predicting their subjective well-being. Participants (N = 198) were undergraduate, graduate, and other status students (in Optional Practical Training) attending U.S. colleges and universities who completed an online survey. Hierarchical multiple regression was used to investigate the moderation model. Results indicated acculturative stress and subjective well-being were negatively correlated. Despite no moderation effects, proactive coping, future time perspective, and perceived English proficiency were associated with subjective well-being. Limitations, future research directions, and implications for clinical practice are discussed.